2017
DOI: 10.3906/vet-1603-26
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nigella sativa and Hypericum perforatum on wound healing

Abstract: IntroductionSkin wounds have long healing processes, and therefore they decrease the life quality of patients. The healing of wounds in a short time without any infections or scars is the desired outcome. In recent years, there have been many studies conducted on alternative treatment methods for wound healing (1-4). The studies related to wound healing aim to achieve wound healing without scar formation as well as accelerating the wound healing (4). However, studies are still ongoing to achieve optimal wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…All articles were published between the years 2010 and 2020. There were four types of wound investigated among the studies, namely excision wound [14,[40][41][42], diabetic ulcers [43][44][45], deep second-degree burn [46,47], and chemical burn [48].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…All articles were published between the years 2010 and 2020. There were four types of wound investigated among the studies, namely excision wound [14,[40][41][42], diabetic ulcers [43][44][45], deep second-degree burn [46,47], and chemical burn [48].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…According to wound depth, three types of wound depths were created, which were superficial partial-thickness wound [40], deep partial-thickness wound [47,48], and full-thickness wound [43,45,46]. The remaining articles [14,41,42,44] did not specify any details about the depth of wound in their studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the articles cited in the present review referred to a total of 79 plants and showed that most of these plants exerted a beneficial effect on skin wound healing. Among these herbal products, A. vera gel [16,38,55,80], C. longa fresh paste/ethanolic extract [22,23,55], and Nigella sativa seed oil and powder [59][60][61] were the most examined. A. vera gel showed significant wound healing activity in comparison to tetracycline ointment [38], soframycin ointment [55], and povidone-iodine [16] via its antibacterial mechanism of action [55].…”
Section: Resultsmentioning
confidence: 99%
“…Fresh C. longa paste [22], polyherbal formulation containing C. longa extract [23], and lotion containing its ethanolic extract [55] increased wound breaking strength, significantly reduced epithelialization, and completed the wound healing process in 15 days. N. sativa oil [59], powder [60], and cream with extract [61] increased epithelialization and granulation as well as demonstrated significant wound contraction rate via its antioxidant activity. It is worth mentioning that most analyzed studies showed the potential of the examined plants in wound healing treatment.…”
Section: Resultsmentioning
confidence: 99%